A new species of Salix (Salicaceae) from Tibet (Xizang), China - He, Li; Liao, Shuai; Zhang, Zhixiang (Phytotaxa, 2014)
We describe and illustrate Salix elongata, a new species of Salix endemic to southeastern Tibet (Xizang). The new species is similar to S. opsimantha in having terminal catkins, oblong bracts, and glabrous ovaries, but differs from the latter as follows: stems decumbent and rooting, petioles long, ovary stipes equal to or longer than the adaxial nectary, styles distinct for half their lengths, stigmas small.